2019
DOI: 10.1021/acs.energyfuels.9b02394
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Thermal Decomposition of Tar in the Presence of Air and Nitrogen Gas

Abstract: Thermogravimetric analysis (TGA) provides useful information, which can be used in thermal processing and conversion kinetic modeling of materials, including hydrocarbons. In the present study, a series of TGA experiments were conducted in the presence of air (combustion) and under inert conditions (pyrolysis) using nitrogen gas with the focus of obtaining quantitative information to compare thermal decomposition characteristics of the two processes. The analysis was performed at different gas injection rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…During thermal decomposition of hydrocarbons including bitumen, several thermochemical processes involving bond breaking and forming, such as vaporization, combustion, oxidative decomposition of carbonaceous organic component, and pyrolysis, take place. [ 11 ] Thus, multiple stages of reactions, which is indicative of existence of the mentioned processes, can be observed from each curve. However, at each heating rate, it shows that the weight loss decreases as the total pressure of the system increases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During thermal decomposition of hydrocarbons including bitumen, several thermochemical processes involving bond breaking and forming, such as vaporization, combustion, oxidative decomposition of carbonaceous organic component, and pyrolysis, take place. [ 11 ] Thus, multiple stages of reactions, which is indicative of existence of the mentioned processes, can be observed from each curve. However, at each heating rate, it shows that the weight loss decreases as the total pressure of the system increases.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetic parameters were obtained using the Arrhenius based method (by solving Equations ( 5) and ( 6)) as presented in our previous studies. [1,9,11] Then, after introducing β in Equation ( 5) and discretizing, Equations ( 12) and ( 13) are obtained as follows:…”
Section: Thermal Decomposition Kinetics and Sa Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al in 2017 constructed a combustion simulation model to match the results of RTO experiment testing combustion reactions between injected air and poststeam oil, which could provide insight into the performance of future pilots . Alade et al (2019) investigated the changes in oil composition under combustion and a pyrolysis process (nitrogen gas injection) and concluded that combustion resulted in a higher conversion rate . Xu et al (2016) reported the impacts of in situ combustion on pore configurations and permeability .…”
Section: Css Follow-up Processes and Simulationmentioning
confidence: 99%
“…Tar residue can cause severe damage in water injection and oil production wells. Alade et al [ 14 ] used thermochemical treatments to remove tar damage, showing that pressure and heat generated due to thermochemical reactions improved tar emulsification and mobilized tar to the surface at a low viscosity. In addition, the authors used the same concept to remove damage due to various organic scales, such as asphaltene and emulsion blockage, in different conditions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%